Greek mothers never die [videorecording (DVD)] - Suissa, Rachel; Suissa, Rachel; Miner, Abby; Rérolle, Simon; Suissa-Fuller, Asia; Sirianni, Carter; Williams, Wade Hunt; Gómez Rosales, Abraham; Perez-Castro, Angelica (Gravitas Ventures, 2025)
Ella dreams of becoming a singer but her Greek mother pressures her daily to take over the family business. After a sudden heart attack, her mother returns to haunt Ella with more advice as Nick, her charming childhood crush, returns.